La protección jurídico penal de la violencia de genero hacia el hombre. Breves reflexiones doctrinales - Córdova Veintimilla, Tommy Eduardo (2025)
Violence is a global phenomenon that, throughout human history, has been characterized by transgressing individual boundaries. This phenomenon can manifest in various forms, causing harm to physical, psychological, economic, or political integrity, among other aspects. Genderbased violence has predominantly been addressed the perspective of women as victims, resulting in specific legal frameworks for their protection. However,this focus has rendered men invisible as potential victims in contexts of gender-based violence. When discussing gender-based violence, the term is often associated exclusively with violence against women, as if the concept of "gender" were limited just to the female sex. This sets the question of whether the male gender is also excluded from this definition. In this context, the United Nations Declaration (1993) defines gender-based violence as: "Any act of violence based on belonging to the female sex that causes or could cause physical, sexual, or psychological harm or suffering to women, including threats of such acts, coercion, or arbitrary deprivation of liberty, whether in public or private life." For this reason, gender-based violence is considered one of the most severe abuses of human rights, as well as one of the most widespread and frequent problems in the fields of justice, public health, and society in contemporary times. This article aims to examine the existing legal and criminal protection for men facing such violence, analyzing legal gaps, relevant doctrines, and challenges in implementing policies that ensure gender-equitable protection. The legal-criminal system must evolve towards a more equitable and inclusive approach, where all victims of gender-based violence, regardless of gender, have access to adequate mechanisms of protection and compensation.